Pembelajaran Organisasi di Era Transformasi Digital: Tinjauan Literatur tentang Peran Learning Agility, Psychological Safety, Dan Psychological Capital pada Karyawan - Andi Syahriana Asdar (INSIGHT: Indonesian Journal Social Studies and Humanities, 2026)
Abstract. Digital transformation has reshaped organizational learning by changing how employees acquire knowledge, share experience, interpret errors, and adapt to technology-enabled work. This article aims to synthesize the roles of learning agility, psychological safety, and psychological capital in strengthening organizational learning among employees. Using an integrative literature review, the article analyzes core international and Indonesian literature on organizational learning, learning agility, psychological safety, psychological capital, digital transformation, Corporate University, servant leadership, and digital talent development. Literature was selected purposively from peer-reviewed journals, academic books, and verifiable scholarly sources published between 1990 and 2026, with classical sources used as theoretical foundations and recent publications used to contextualize digital transformation. The synthesis indicates that learning agility functions as adaptive learning capacity, psychological safety as a safe interpersonal climate for dialogue and error-based learning, and psychological capital as positive psychological resources that sustain hope, efficacy, resilience, and optimism during change. The article proposes an integrative framework in which individual adaptive capacity, team learning climate, and positive psychological resources interact to support organizational learning in the digital transformation era.Keywords: organizational learning; learning agility; psychological safety; psychological capital; digital transformation